Summative Assessment Reconstruction on Negotiation Text for the Tenth Grade in Vocational School - Nikmah, Faridhatun; Wafiq, Chici Al; Ahmad, Affan Ghaffar; Hidayah, Nasik; Wulandari, Mely; Wagiran, Wagiran; Naryatmojo, Deby Luriawati (Universitas PGRI Semarang, 2024)
The purpose of this research was to determine the quality of summative assessment tests in three modules of negotiation texts class X SMK at the vocational level. The quality of the questions is very influential on the results Â of achieving the learning objectives of students as a basis for determining class increase or graduation from educational units. This research was conducted by analyzing (1) assessment qualifications in the module, (2) the level of difficulty of the questions, and (3) the cognitive level of the questions. The method used in this study is qualitative method with techniques by interviews and literature studies. The results showed that the application of summative assessment at SMKN 1 Bangil used more C4 reaching 50%. In addition, the difficulty level of the questions is categorized as good because the medium level has reached 50%. At SMKN 2 Purwosari shows more dominant use of C2 in the form of understanding of problems that have been learned in previous learning. This indicates the need for cognitive improvement in the problem to achieve balance. In addition, the difficulty level of the questions is categorized as good because the medium level has reached 50%. Furthermore, in the SMKN 2 Jepara module, more operational verbs use to apply (C3) and create (C6) which reaches a percentage of 26.7%. Through this analysis, there are several problems that have not been balanced in difficulty and cognitive levels and there needs to be reconstruction to achieve better student learning outcomes.